Review on green building rating tools worldwide: recommendations for Australia - Illankoon, I. M. Chethana S.; Tam, Vivian W. Y.; Le, Khoa N.; Tran, Cuong N. N.; Ma, Mingxue (Journal of Civil Engineering and Management, 2019)
Buildings could be led to adverse impacts on environment, such as generation of construction and demolition waste, and emission of greenhouse gases (GHG). Therefore, promotion on development of green buildings is in need. With the increasing awareness in sustainable development, various rating tools are promoted to evaluate the performance of green buildings. Nowadays, these tools function as a guideline for green building development. There are various green building rating tools developed worldwide, and various countries follow different rules, incentives and regulations. However, despite of promotion of green building rating tools, environmental issues from buildings are still significant in Australia. This research compared green building rating tools in Australia and other countries or regions around the world. This research found that rating tools in Australia lack of (1) mandatory criteria and (2) regulations and incentives. This paper recommended that governmental incentives should be promoted.